Inhibitor development after switching of FVIII concentrate in multitransfused patients with severe haemophilia A. (3rd April 2014) - Aznar, J. A.; Moret, A.; Ibáñez, F.; Vila, C.; Cabrera, N.; Mesa, E.; Bonanad, S.
Summary: Switching between different therapeutic FVIII concentrate types has been postulated as a possible cause of inhibitor development in patient with haemophilia A. In this single‐centre, retrospective study, the incidence, titre and duration of inhibitor development in multitransfused patients, defined as patients with more than 150 exposure days (ED), were analysed from January 1970 to December 2007 in relation to ED and the number of switches between different products. Inhibitor titre was assessed by Bethesda assay (before 1998) or Nijmegen assay (after 1998). Medical records of 167 patients were screened, of which 97 patients met the inclusion criteria. Fourteen products of plasmatic origin (different purities) and five recombinant (three generations) were used. Nine patients (9%) developed inhibitors, all transient, low‐titre (1.41 ± 0.54 BU) after 323 ± 287 ED in average. Seventeen patients had no product switches of which four patients (23%) developed inhibitors (97 ED in average), whereas 13 patients (77%) did not (ED: 230). Fifty patients switched between plasmatic products only (median: 10 changes) of which five patients (10%) developed inhibitors (ED: 503), whereas 45 patients did not (ED: 932). Five patients switched between recombinant products only (seven changes) of which no patient developed inhibitors (748 ED). Twenty‐five patients switched between plasmatic and recombinant products (13 changes) of which no patient developed inhibitors (ED: 1654). No statistically significant differences between patient groups were observed. Neither the number of different FVIII products administered nor the switching of products influenced the incidence of inhibitor in multitransfused patients.